Study of Satisfaction Level of Hostel Students on Sultan Mizan Zainal Abidin Polytechnic Cafeteria Services - WAN MAHMOOD, WAN SALMIZI (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study analyzes the level of satisfaction from hostel students on food service at the cafeteria of Sultan Mizan Zainal Abidin Polytechnic (PSMZA). There are 4 factors studied in this study that are expected to contribute to the level of student satisfaction with cafeteria services, namely the cleanliness of the cafeteria, food prices, variety of menus and cafeteria facilities. The results of the study showed that the level of students’ satisfaction with the food service in the cafeteria was at a bad level. All the factors studied contribute to the level of students’ satisfaction. This study also provides suggestions to improve the level of students’ satisfaction with the quality of life in the hostel and suggestions for further research that can be done to ensure the quality of food and food preparation services in the Sultan Mizan Zainal Abidin Polytechnic Cafeteria.